Arisan Dalam Perspektif Akuntansi - Riani Sukma Wiajaya; Nini Nini; Khadijah Ath Thairah (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
This research aims to analyze social gatherings from a accounts receivable accounting perspective, the method in this research is descriptive qualitative interpretive approach. This research will reveal the experiences of research informants regarding social gatherings attended in Padang City. The selection of informants is people who are in the community and have the capability to explain the phenomena they experience. The observation area is determined randomly based on the opportunity the researcher has to carry out observations and interviews and social gathering models that are not found in other areas. Data analysis techniques refers to the Miles, Huberman, and Saldana model. In this research, reduction was carried out simultaneously with data collection so that information was obtained relating to the informant's perspective on arisan activities from a receivables or information perspective. Based on the discussion above, it can be concluded that members' desire to participate in arisan is based on the number of members' desire to save and their awareness of money. collected is closer to recognizing a receivable and if collected early will tend to be considered an investment. Another economic motive is the tendency of some people to use social gatherings as an instrument to obtain investment funds. Some people even use social gatherings as a means of investment by handing over goods or money equivalent to goods with the aim of saving money from the effects of inflation.